Identifikasi Jenis Pesan Politik Pilpres 2019 Pada Facebook Pemilih Milenial Di Kendari - Hardika Vebriana; Muhammad Zein Abdullah; Sutiyana Fachruddin (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2019)
ABSTRACTThis study aims to determine the message categories, message issues and the number of political messages on Facebook social media in the Presidential Election 2019. This research method uses qualitative methods with the subject of this research are millennial voters in Kendari City who actively use Facebook social media and have uploaded political messages in the Presidential Election 2019. The number of research informants is 10 people. The technique for determining informants in this study is purposive sampling technique. The data collection techniques used are observation, interviews, documentation and literature study. This study found that the categories upload of political messages in the Presidential Election 2019 contained in the millennial voter Facebook account in Kendari, there contained five types of messages namely political participation, government policy, electoral fraud, political campaigns and figures of Presidential candidates. FKeywords: Types of Political Messages, Facebook, Millennial voters